Debriefing’s Influence on Learning in Business Game: An Experimental Design - Adonai Jose Lacruz (FUCAPE Business School, 2018)
This paper studies the influence of debriefing in the learning of the participants of business games. Through quasi-experimental study we examined the self-declarations of 112 undergraduate Business Management students undertaking the 8th term, divided into two groups: experimental, exposed to debriefing; and control, not exposed to the debriefing. MannWhitney´s tests revealed that the quantum of learning perceived by the members of the experimental group was statistically significantly higher than the members of the control group in seven out of nine learning variables assessed (p < 0.05). The average effect size (d = 0.45) shows an average improvement of 18%. These results suggested that the debriefing positively influence on experiential learning cycle promoted by business games. In the perspective of Kolb’s experiential learning cycle (Kolb, 1984), our findings suggest that Reflective observation and Abstract conceptualization stages can be reinforced by subsequent debriefing activities to the simulation rounds, in order to enhance continuous processes of action and reflection of the participants, according to the spiral experiential learning cycle.